Effect of sweet solutes on the quality of a pumpkin puree (Cucurbita moschata, Duchesne ex Poiret) preserved by the hurdle technology - Gliemmo, María Fernanda (2010)
The effect of glucose and xylitol on the quality of a pumpkin puree preserved by the hurdle technology was studied. It was demonstrated that the addition of glucose or xylitol to depress water activity (Aw) to 0.98 was necessary to assure 3 weeks of microbial stability at 25C of a pH 4.00 pumpkin puree, containing potassium sorbate and submitted to vapor heat treatment. A decrease in a and b color parameters was observed during storage for both humectants. However, the use of a low oxygen permeability packaging such as polyvinyl chloride-polyvinylidene chloride copolymer instead of polyethylene protected the color. From a rheological point of view, xylitol diminished yield stress and consistency coefficient independently of storage time. The results obtained emphasize the advantage of the use of glucose as well as the importance of an appropriate choice of solutes to depressAw in order to improve the quality of pumpkin puree.